Effect of electrical discharge on the properties of natural esters insulating fluids - Imran Sutan Chairul; Sharin Ab Ghani; Nur Hakimah Ab Aziz; Mohd Shahril Ahmad Khiar; Muhammad Syahrani Johal; Mohd Aizzat Azmi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Vegetable oils have been an alternative to mineral oil for oil-immersed transformers due to concern on less flammable, environmental-friendly, biodegradable, and sustainable resources of petroleum-based insulating oil. This paper presents the effect of electrical discharges (200 up to 1000 discharges) under 50 Hz inhomogeneous electric field on the properties (acidity, water content, and breakdown voltage) of two varieties of vegetable based insulating oils; i) natural ester (NE) and ii) low viscosity insulating fluids derived from a natural ester (NELV). Results show the water content, acidity and breakdown voltage of NE fluctuate due to applied discharges, while NELV display insignificant changes. Hence, results indicate that the low viscosity insulating fluids derived from natural ester tend to maintain their properties compared to natural ester.